INTERNET USE AND MENTAL HEALTH IN AFRICA AND INDIA - Shrum, Wesley Monroe; Yevuyibor, Jonathan Teye; Thakkar, Shriya (AoIR Selected Papers of Internet Research, 2021)
Prior research has shown that mental health in urban slums is associated with the a share number of older individuals in personal networks. This presentation will examine the extent to which that association is mediated through Internet and social media use. We conducted face to face interviews with residents (minimum 18 years) in two high density, low income areas of Accra (West Africa) and Trivandrum (Kerala, India), where local teams have conducted repeated studies of personal networks since 1994. Our preliminary results show that mobile phones are primary way in which respondents communicate with members of their core networks. Further preliminary results show that while research in high income areas has generally shown the importance of larger networks for positive mental health, our analysis of urban slums reveals a different pattern. First, there is no general association of larger networks with reduced symptoms of anxiety and depression. Second, one particular group of relationships is strongly associated with depression and anxiety: ties with older individuals. The questions we explore are: (1) To what extent are indicators of mental health related to indicators of Internet and social media usage? (2) To what extent are indicators of mental health related to indicators of social network size and composition? (3) To what extent are indicators of Internet and social media usage related to indicators of indicators of social network size and composition?